The Art of Designing Behaviour : mastering a Practical Method to Influence Decisions and Shape Desired Behaviours - Groenewegen, Astrid, ....- (Amsterdam : Boom, 2022)
People are complex beings and so is behavioural change, but you'll be able to do more than you think possible. And once you understand how people arrive at decisions, you will find yourself with gold in your hands. Marketeers, policy-makers, HR-professionals, managers - and also even you yourself. Almost all of us are coping with the question how we might influence human behaviour. One thing is clear: changing behaviour is pretty difficult. But why is this so? And how might you in fact manage to do it? The Art of Designing Behaviour takes you along to the missing link: applied behavioural science. How do we arrive at our choices? What triggers us to undertake an action? And what actually prevents us from doing so? This knowledge is at the basis of the SUE Behavioural Design Method(c), which has already been successfully used for a decade in organisations all over the world. This book is both a masterclass and a toolbox combined. You are trained in an accessible method, and will learn what principles and mechanisms you may use in order to stimulate desirable behaviour. Before you know it, you'll be bursting with ideas in order to have a pleasant go at tackling your problem and helping people to make better choices. Recommendation: 'I have read many works on behavioural design that helped me understand the theory of influence. This book finally enables me to put it to practice. Brilliant!' - Klaas Dijkhoff, former Dutch minister and parliamentary leader
Keywords: Behaviour design; Psychology